2017
DOI: 10.1159/000484061
|View full text |Cite
|
Sign up to set email alerts
|

Nogo-B Promotes Angiogenesis in Proliferative Diabetic Retinopathy via VEGF/PI3K/Akt Pathway in an Autocrine Manner

Abstract: Background/Aims: Nogo-B, a conservative protein of endoplasmic reticulum, is a member of the reticulon family of proteins. Proliferative diabetic retinopathy (PDR) is the major concerning problem of diabetic retinopathy. This study explored the role of Nogo-B in the regulation of angiogenesis in PDR patients and primary human retinal endothelial cells (HRMECs). Methods: Nogo-B was down-regulated through the use of Lentivirus-NogoB-RNAi, the effects of Nogo-B on angiogenesis under high glucose stimulation were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Angiogenesis develops a neovascular network, which requires not only ECs but also the cooperation of PCs and SMCs [30,31]. The newly formed vessels were initiated by ECs and matured by PCs and SMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis develops a neovascular network, which requires not only ECs but also the cooperation of PCs and SMCs [30,31]. The newly formed vessels were initiated by ECs and matured by PCs and SMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Visual loss primarily occurs due to increased permeability of retinal vessels (diabetic macular edema) [3] and retinal neovascularization (proliferative diabetic retinopathy) [4,5]. As DR pathogenesis is multifactorial [6][7][8], precise molecular mechanisms therein are still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The data demonstrated that phosphorylation of FAK was essential for the migration of hDPSCs, and this finding is in accordance with the role of FAK in MSCs . Previous studies have identified that the PI3K/Akt pathways induce proliferation and migration of various cells in response to VEGF (Zhang et al 2017, Huang et al 2018). Previous studies have identified that the PI3K/Akt pathways induce proliferation and migration of various cells in response to VEGF (Zhang et al 2017, Huang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…PI3K participates widely in the multiple cell migration process by coordinating protein localization and conformation through activation or recruitment of pleckstrin homology domaincontaining proteins, including the protein kinase Akt (Lien et al 2017). Previous studies have identified that the PI3K/Akt pathways induce proliferation and migration of various cells in response to VEGF (Zhang et al 2017, Huang et al 2018). In the present study, wound healing assay and migration assays were performed with PI3K-specific inhibitors (LY294002) and Figure 5 VEGFA mediated migration of hDPSCs via VEGFR2 rather than VEGFR1 (a) After transfection with siVEGFR2 or siVEGFR1 for 48 h, hDPSCs were detected with Western blot and exposed to the indicated antibody.…”
Section: Discussionmentioning
confidence: 99%